As tecnologias da informação e comunicação (TIC) no contexto escolar para o ensino de ciências - FURTADO, Jhennyfer Miranda (2024)
Discussions about the insertion of Information and Communication Technologies (ICT) in the school context are growing, considering the technological advances that emerge in society. Therefore, the use of these resources in the educational field becomes indispensable when analyzing the contributions that they can bring to a better teaching and learning process. The work aims to verify the importance of technological inclusion as a support in science classes, emphasizing how teachers are inserting this teaching tool in their methodologies through the intervention process in the municipal education network of Cametá-PA, through the use of technological resources of information and communication in science teaching. The methodological theoretical process took place in two ways; a priori, a bibliographic survey was carried out; where some references of authors such as: PAULO FREIRE (2013), LIBÂNEO (1994), KENSKI (2007, 2012), BRASIL (1998) were sought, and later the field research was carried out, through the application of questionnaires, with the students active in the Municipal network of Cametá-PA of elementary education in science class. Therefore, it is noted how much the use of ICT in schools contributes to the teaching and learning of students, always aiming at the search for new knowledge. This study presents contributions to broaden the view on the use of ICT as a resource in the classroom, as well as tools that motivate and generate a rapprochement between teachers and students, transforming the school environment into an interactive and dynamic space.